Owner experience and veterinary involvement with unlicensed GS-441524 treatment of feline infectious peritonitis: a prospective cohort study - Negash, Rosa; Li, Emma; Jacque, Nicole; Novicoff, Wendy; Evans, Samantha J. M. (Frontiers in Veterinary Science, 2024)
Feline Infectious Peritonitis (FIP) has historically been a fatal coronaviral disease in cats. In recent years, the therapeutic agent GS-441524, developed by Gilead Sciences, was found to be a successful treatment for FIP in most patients in clinical trials. However, this particular drug has remained stalled in the therapeutic pipeline, leaving patients and cat owners without a licensed medication. In the meantime, online social media platforms began to emerge, connecting cat owners with a community of citizen non-veterinary professionals sourcing unlicensed GS-441524. This study prospectively followed participants (N=141) that successfully completed 12 weeks of treatment, capturing their treatment experiences with self-administered GS-441524-like medication. A one-time survey was administered to enrolled participants with mixed format of questions (open-ended and multiplechoice) asking about treatment administration techniques, observed side effects of GS-441524, accrued cost, veterinarian involvement, impact on the cat-human bond, and social media usage. Our results show cat owners experienced a shift in treatment modality from injectable GS-441524 to pill formulation across the treatment period. The average total cost of medication has decreased since 2021 to approximately USD 3100, and participants reported the human-animal bond being affected negatively. Additionally, there was an increased trend in veterinarian awareness of GS-441524-like therapeutics and monitoring of clients undergoing treatment. Social media usage was reported as being important at the beginning of treatment to establish treatment administration but lessened by the end of treatment. This study is the first detailed, prospective account of owner experiences with unlicensed GS-441524, raising an important discussion surrounding citizen veterinary medicine.